2021
DOI: 10.1103/physrevd.103.023522
|View full text |Cite
|
Sign up to set email alerts
|

Imprint of relativistic particles on the anisotropies of the stochastic gravitational-wave background

Abstract: The Stochastic Gravitational-Wave Background (SGWB) is expected to be a key observable for Gravitational-Wave (GW) interferometry. Its detection will open a new window on early Universe cosmology, on the astrophysics of compact objects and, as shown in this Letter, on the particle physics content of the Universe. In this Letter we show that, besides their effects on the Cosmic Microwave Background (CMB) and on Large Scale Structure (LSS), relativistic particles in the early Universe leave a clear imprint on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 60 publications
3
63
0
Order By: Relevance
“…Instead of the energy spectrum of GWs from topological defects, we also find the anisotropies of those stochastic GW backgrounds carry unique information about inflation. The anisotropies in stochastic GW backgrounds could be generated by the sources [196,[207][208][209] and the processes during propagation [210][211][212][213], which in most cases are still challenging to observe [214][215][216][217][218][219]. We explore the SGWB produced from unstable cosmic domain walls, which annihilates before dominating the Universe [220,221].…”
Section: (4) Particle Physics Phenomenology On the Phase Transition Modelsmentioning
confidence: 99%
“…Instead of the energy spectrum of GWs from topological defects, we also find the anisotropies of those stochastic GW backgrounds carry unique information about inflation. The anisotropies in stochastic GW backgrounds could be generated by the sources [196,[207][208][209] and the processes during propagation [210][211][212][213], which in most cases are still challenging to observe [214][215][216][217][218][219]. We explore the SGWB produced from unstable cosmic domain walls, which annihilates before dominating the Universe [220,221].…”
Section: (4) Particle Physics Phenomenology On the Phase Transition Modelsmentioning
confidence: 99%
“…The formalism has been used to compute the spectra of the anisotropies induced by extra-relativistic degrees of freedom in Ref. [36], where it was shown that the early decoupling of gravitons makes them an excellent observable to constrain the physics of the early Universe. Their cross-correlation with CMB temperature anisotropies has instead first been considered in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Tools and techniques to measure anisotropic components of the SGWB have been developed in [29][30][31][32][33][34][35][36][37]. The physics that governs SGWB anisotropies (at least in the geometric optics limit) displays strong analogies with that underlying Cosmic Microwave Background (CMB) fluctuations [38][39][40][41]. Moreover, General Relativity predicts a non-zero spatial corre-lation between the SGWB and the CMB, since gravitons share their perturbed geodesics with CMB photons.…”
mentioning
confidence: 99%
“…Here, in the case of the CGWB, we include the impact of different effects (i.e., Sachs-Wolfe (SW), ISW and Doppler) on the spectrum and we give a physical interpretation of its features at different multipoles. Following [41], we modify the publicly available Boltzmann code CLASS [45] and we extract both the CGWB×CGWB auto-correlation and the CGWB×CMB angular cross-spectrum. We then perform a Signal-to-Noise Ratio (SNR) analysis for these crosscorrelation signals and find a detectable correlation between the two backgrounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation